Challenges and Problems of Learning Islamic Religious Education in the Digital Era - Yeri Nofrianti; Arifmiboy Arifmiboy (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2021)
AbstractThis study explains the challenges and solutions to problems that arise related to the presence of a digital based technology world, one of which leads to the world of Islamic education. Islamic religious education must reform and innovate its system. Because if this is not done, then Islamic Religious Education will be left behind, especially in relation to the learning process in the classroom. Currently, the presence of a sophisticated technology based learning model will certainly be a challenge and a separate problem for Islamic Religious Education, especially in the learning process that will be carried out, is Islamic Religious Education able to compete and not be left behind in today's digital era. This issue is certainly quite complicated for all related elements, because situations like this have never happened before. The research method used is Library Research, where the data taken comes from writings and literature that support this research. Preliminary findings show that today PAI must be able to compete and leave conventional ways to reform in accordance with the current situation. PAI is considered necessary to find solutions to the challenges and problems of Islamic Religious Education because this is an important aspect in the world of Islamic education, especially in order to be able to give birth to civilized humans and future leaders in accordance with Islamic teachings.Keywords: Challenges and Problems, Learning Islamic Religious Education, Digital EraAbstrakPenelitian ini menjelaskan tentang tantangan dan solusi dari permasalahan yang muncul berkaitan dengan hadirnya dunia tekhnologi berbasis digital, dimana salah satunya mengarah kepada dunia Pendidikan Islam. Pendidikan Agama Islam harus melakukan pembaharuan dan inovasi terhadap systemnya. Karena jika ini tidak dilakukan, maka Pendidikan Agama Islam akan semakin tertinggal, terutama dalam hubungannya dengan proses belajar di kelas. Saat ini hadirnya model pembelajaran berbasis tekhnologi yang canggih tentu akan menjadi tantangan dan problematika tersendiri bagi Pendidikan Agama Islam khususnya dalam proses pembelajaran yang akan dilakukan, apakah Pendidikan Agama Islam mampu bersaing dan tidak tertinggal dalam era digital hari ini. Persoalan ini tentu cukup pelik dirasakan oleh semua unsur yang terkait, karena situasi dan keadaan seperti ini belum terjadi sebelumnya. Metode penelitian digunakan adalah Library Research, dimana data yang diambil berasal dari tulisan dan literatur yang mendukung penelitian ini. Hasil temuan awal menunjukkan bahwa hari ini PAI harus mampu bersaing dan meninggalkan cara-cara konvensional menuju pembaharuan yang sesuai dengan keadaan saat ini. PAI dianggap perlu mencarikan solusi atas tantangan dan problematika Pendidikan Agama Islam karena hal ini merupakan aspek penting dalam dunia Pendidikan Islam khususnya agar mampu melahirkan manusia beradab dan pemimpin masa depan yang sesuai dengan ajaran Islam.Kata Kunci: Tantangan dan Problematika, Pembelajaran Pendidikan Agama Islam, Era Digital